Diseño, simulación y fabricación de un equipo mecánico alineador de ejes para generadores de corriente alterna utilizados en centrales hidroeléctricas. (2023)
In the power generation industry, shaft misalignment on rotating machines is considered a common failure. Improper alignment of rotating shafts often leads to serious vibration complications, with premature failure of machine parts.